Indigenous theology and the western worldview : a decolonized approach to Christian doctrine - Woodley, Randy, 1956- (Grand Rapids Baker Academic, 2022)
"A Cherokee teacher, missiologist, and historian encourages us to reject the many problematic aspects of the Western worldview and to convert to a worldview that is closer to that of Jesus"--
Includes bibliographical references and index.
Keywords: Postcolonial theology; Theology; Indians of North America -- Religion